THEORETICAL BASICS OF INTERNATIONAL TOURISM RESEARCH - PANOVA, Iryna; HLADUKHOVA, Yeva (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of the theoretical foundations of international tourism research. It is noted that foreign experience can help the tourism industry of other countries to attract foreign investments, create new jobs and improve the quality of tourist services. The essence of the concept of "international tourism" has been defined. The socio-economic prerequisites for the development of international tourism have been studied. It is noted that tourism is one of the most dynamically developing branches of the world economy, which makes a significant contribution to the social, cultural and economic development of countries. Ukraine, as a large Eastern European country, has a powerful tourism potential, but it is not yet fully utilized. The relevance of the study of the development of tourism in Ukraine based on the European experience is the need to evaluate and adapt the best practices of the tourism industry, which are successfully applied in the European Union and other countries. The introduction of European experience can contribute to the effective development of tourism in Ukraine, attracting more foreign tourists, increasing the amount of foreign exchange earnings and raising the standard of living of the population. In this diploma work, we propose to conduct a detailed analysis of the European experience in the field of tourism and explore the possibilities of its implementation in Ukraine. The research is aimed at identifying advanced strategies and tools for tourism development that could be successfully adapted to Ukrainian conditions. The object of research is international tourism. The subject of the study is the experience of the development of international tourism. Consequently, the consequences of globalization and growing international cooperation have become essential for the development of international tourism in EU countries. Socio-economic preconditions play an important role in stimulating and supporting this sector, which has become a key driver of economic growth and cultural exchange in the EU.
Keywords: international tourism; tourism industry; sustainable development of tourism